Relationship between sprint performance and muscle fascicle length in female sprinters - Abe, T.; Fukashiro, S.; Harada, Y.; Kawamoto, K. (Journal of Physiological Anthropology, 2001)
The purpose of this study was to investigate the relationship between sprint performance and architectural characteristics of leg muscles in 26 female 100-m sprinters. Pennation angle and muscle thickness of the vastus lateralis (VL) and gastrocnemius medialis (GM) and lateralis (GL) muscles were measured by B-mode ultrasonography, and fascicle length was estimated. Sprinters had a significantly lower VL pennation angle, but GM and GL pennation angle was similar between sprinters and female control subjects (N=22). There was no significant correlation between pennation angle and 100-m personal best performance. Sprinters had significantly greater absolute fascicle length in VL and GL than controls, which significantly correlated to 100-m best-record (r=-0.51 and r=-0.44, respectively). Relative fascicle length (VL and GL) were also significantly greater in sprinters than controls. However, there were no significant correlation between relative fascicle length and 100-m best-record (r=-0.36 and r=-0.29, respectively). No relationship was found between the sprint performance and fat-free mass (r=-0.26) or body mass index (r=-0.03). However, there was a significant correlation between percent (%) body fat and 100-m best-record (r=0.62, p<0.01). Adjusting the confounding effect of % fat, significant correlations were seen between relative fascicle length and 100-m best-record (VL; r=-0.39 and GL; r=-0.40). Absolute and relative fascicle length were similar in elite female sprinters compared with previous reported values for elite male sprinters (Kumagai et al., 2000). It was concluded that longer fascicle length is associated with greater sprinting performance in sprinters, but there is no gender differences in fascicle length for elite sprinters.